A profile of selected psychiatric out-patients in South Africa - L. R. Uys; N. K. Dlamini; S. P. Mabandla (AOSIS, 1995)
This article reflects the results of three studies done between 1988 and 1991 describing psychiatric outpatients in different towns and cities of South Africa. Two of the samples consist of Black patients and one of Asian patients. In all three studies demographic, socio-economic and illness data were gathered and analysed. A total of 230 patients were surveyed. The typical psychiatric outpatient seems to be in productive period of his life, single, but living with family. He is poorly educated, may never have been employed and is probably now unemployed. The income of this person and the household is very limited, with many people dependent on the few ecomonically active members of the household.